Applying three decades of research to mitigate the impacts of hemlock woolly adelgid on Ontario’s forests - William C. Parker; Victoria Derry; Ken A. Elliott; Chris J.K. MacQuarrie; Sharon Reed (The Forestry Chronicle)
Over the past 70 years, the introduced, invasive hemlock woolly adelgid (Adelges tsugae Annand) has become established and caused considerable decline and mortality of eastern hemlock (Tsuga canadensis (L.) Carr.) across much of the tree’s natural range. Hemlock is a foundation tree species with little inherent resistance to this exotic species and infestation by this sap-feeding insect results in progressive crown decline and tree mortality within 4 to 15 years. Continued climate warming favours the spread of this insect to Ontario and other areas at the northern edge of hemlock’s range. More than 30 years of basic and applied research directed towards control and mitigation of damage by this insect indicates that the rate of development of hemlock decline and mortality depends on climate, site, and stand factors that affect both insect performance and hemlock vigour. Here we synthesize these research findings to provide science-based management recommendations to (1) increase the resilience of Ontario’s hemlock forest resource to this insect before it spreads, (2) mitigate hemlock woolly adelgid damage once it gets established, and (3) facilitate degraded hemlock forest restoration.